AICCRA Gender and Social Inclusion: Looking Forward in Gender Smart Agriculture - Huyer, Sophia; Gondwe, Therese (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
AICCRA has evolved its approach to gender and social inclusion (GSI) from targeting women for inclusion in CSA and climate information, to one of integrating gender-responsive and -transformative approaches into CSA/CIS innovation packages. It has developed a set of frameworks for GSI, including CSA prioritization and consultation that enables women and youth, GSI analyses, the Gender Smart Agriculture approach that frames gender equality in relation to resilience, and the Gender and Climate Empowerment Index. Greater attention is needed relating to innovative capacity of women and youth in value chains. Scaling in a gender and socially-inclusive manner is an emerging and critical challenge